The Role Of Human Resource Management In Organizations - Ading Rahman Sukmara (SEAN Institute, 2024)
Human resources (HR) that play a role as the core of development. HR management addresses various management issues, ensuring effective use of HR through organizational systems. Overall, HR management is vital to achieving corporate goals. Human Resources in macro terms refer to the number of people in a country, but currently focus more on employees of an organization. HR includes individuals with skills and mental and physical strength, which are important in the development process of countries, companies, and organizations. Research methods involve statistical analysis, budgeting, innovation, and computer modeling to ensure that human resource planning is in accordance with institutional needs. Qualitative research is used to describe, explain, and analyze human resource phenomena, focusing on human attributes in business. Human resource adequacy also involves motivational factors, salary, and workplace comfort, as well as psychological contracts between individuals and organizations.